2019
DOI: 10.1515/pac-2019-0108
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic betalain as antioxidants: meta means more

Abstract: Betalains are phytochemicals of nutraceutical importance that emerged as potent antioxidants, preventing radical chain propagation and the deleterious health effects of oxidative stress. However, despite the wide application of betalains as color additives in products for human consumption, little is known about the relationship between their structure and antioxidant potential. Here we investigate the mechanism of antioxidant action of three regioisomeric phenolic betalains and show that the meta isomer has h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 57 publications
2
11
0
9
Order By: Relevance
“…The product was isolated in 50% yield after purification in the presence of oxygen, which is twice as high as the values reported for other betalains. 20,26 The high-resolution mass spectrum was consistent with the postulated structure of OxiBeet (Fig. 1b).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The product was isolated in 50% yield after purification in the presence of oxygen, which is twice as high as the values reported for other betalains. 20,26 The high-resolution mass spectrum was consistent with the postulated structure of OxiBeet (Fig. 1b).…”
Section: Resultssupporting
confidence: 70%
“…Last, these findings highlight the importance of the 1,7-diazaheptamethinium system of betalains for their striking antioxidant properties. 20,34 Ultrafast transient absorption experiments were carried out to determine whether photoexcitation plays a role in the autoxidation of OxiBeet. In aerated water, the electronic excitation of OxiBeet at 485 nm results in ground state bleaching (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…b Species refer to the parent species and the deprotonation site (Figure 3c). c from Reference [27].…”
Section: Figurementioning
confidence: 99%
“…The antioxidant capacity of betanin is comparable to that of ECG due to the presence of a 5- O -glucosyl catechol moiety and a 1,7-diazaheptamethinium [23] system [24,25,26]. We have found that N -(3-hydroxylphenyl)betalain ( m -OH-pBeet) is an adequate model to study the mechanism of antioxidant action of betanin because they share the same radical scavenging capacity [27]. Although the antioxidant action of m -OH-pBeet was rationalized in terms of proton-coupled electron transfer (PCET), the importance of the 1,7-diazaheptamethinium system for the antioxidant potential of betalains could not be elucidated [27].…”
Section: Introductionmentioning
confidence: 99%